Promoting high T2 contrast in Dy-doped MSNs through Curie effects. Issue 2 (16th December 2021) - Ellis, Connor M.; Pellico, Juan; Young, Liam A. J.; Miller, Jack; Davis, Jason J.
Abstract : The dominant Curie effect underpinning relaxivity enhancements in T 2 has been systematically tuned through paramagnetic loading density. This results in the optimisation of acquired MR image contrast, and facilitates effective high field imaging. Abstract : Contrast agents retaining high relaxivities at ultrahigh magnetic fields underpin an enhanced image sensitivity within derived MRI scans. By varying the Dy 3+ loading density inside a mesoporous silica architecture the dominant Curie effect can be effectively tuned so as to optimise T 2 contrast at magnetic fields as high as 11.7 T.